SOCIAL IMPACT OF MANGROVE LAND CONVERSION IN DIMENSIONS AS RURAL SUSTAINABILITY - A Hadian Pratama; Budi Gunawan; Budi Cahya (Jurnal Ilmiah Peuradeun, 2016)
Mangrove ecosystem is an important part of the coastal environment. One of the problems in almost all coastal areas in Indonesia is the degradation of mangrove area. In the coastal areas of Langkat Regency, precisely in the Tapak Kuda Village is also facing the same thing. In the last 15 years, mangrove area has reduced quite high. One of them is caused by the conversion of mangrove land into ponds. The existence of mangrove ecosystems is related to socio-economic life of society that causes the decline of mangrove area and the changing environmental conditions of social life. The results showed that the conversion of mangrove land brought the social impact on residents’ lives. Changes in the types of jobs are fishermen decreased 24%, the percentage of farmers rose 19% and fish farmers also rose 10%. Income-related conditions, 24% of people feel steady and have sufficient income to meet the families’ needs, 43% of people feel sometimes high income is not enough to meet families’ needs and 33% of people feel low income that make the families’ needs are not fulfilled. The condition of public education level has increased, the percentage of people completing primary school rose 7%, junior high was up 21%, and high school 16%. Regarding the use of natural resources, there were only 35% of the natural resources that could be managed by the community. Community land use patterns are 10% of ponds, 30% of fields, 20% of fishing areas and 40% of conservation areas.